Differential cytokine sensitivities of STAT5-dependent enhancers rely on Stat5 autoregulation. Issue 21 (30th September 2016) - Willi, Michaela; Yoo, Kyung Hyun; Wang, Chaochen; Trajanoski, Zlatko; Hennighausen, Lothar
Abstract: Cytokines utilize the transcription factor STAT5 to control cell-specific genes at a larger scale than universal genes, with a mechanistic explanation yet to be supplied. Genome-wide studies have identified putative STAT5-based mammary-specific and universal enhancers, an opportunity to investigate mechanisms underlying their differential response to cytokines. We have now interrogated the integrity and function of both categories of regulatory elements using biological and genetic approaches. During lactation, STAT5 occupies mammary-specific and universal cytokine-responsive elements. Following lactation, prolactin levels decline and mammary-specific STAT5-dependent enhancers are decommissioned within 24 h, while universal regulatory complexes remain intact. These differential sensitivities are linked to STAT5 concentrations and the mammary-specific Stat5 autoregulatory enhancer. In its absence, mammary-specific enhancers, but not universal elements, fail to be fully established. Upon termination of lactation STAT5 binding to a subset of mammary enhancers is substituted by STAT3. No STAT3 binding was observed at the most sensitive STAT5 enhancers suggesting that upon hormone withdrawal their chromatin becomes inaccessible. Lastly, we demonstrate that the mammary-enriched transcription factors GR, ELF5 and NFIB associate with STAT5 at sites lacking bona fide binding motifs. This study provides, for the first time, molecular insight into the differential sensitivities of mammary-specific and universal cytokine-sensing enhancers.